A novel durable spinel-type ZnGa2O4 transparent ceramic with wide transmission range. (December 2021) - Wang, Bin; Wang, Hao; Chen, Bowen; Xu, Pengyu; Chen, Qiangguo; Tu, Bingtian; Wang, Weimin; Fu, Zhengyi
Abstract: A novel ZnGa2 O4 transparent ceramic was prepared from synthesized single-phase powders by pressureless sintering combined with hot isostatic pressing (HIP) and a post-annealing treatment. The transparent ceramic was fully densified with the average grain size of ∼3.2 μm, which possesses outstanding optical properties, including a high in-line transmittance of 82.03% at 2 μm comparable to its single crystal counterpart (82.52% at 2 μm) and a wide transmission range (0.27-8.7 μm). Such an extended infrared transmission range could be attributed to the lower phonon frequency of ZnGa2 O4 spinel. This material also exhibits excellent mechanical properties of Vickers hardness (10.56 ± 0.08 GPa), Young's modulus (227.04 GPa) and fracture toughness (1.83 ± 0.08 MPa/m 1/2 ), as well as high thermal conductivity (19.46 W/mK) at ambient temperature. Graphical Abnnstract: Image, graphical abstract